Impact Of EWS Implementation On The Quality Of Inpatient Services In Indonesian Hospitals : Literature Review - Vica Firdausa (International Journal of Health Engineering and Technology, 2026)
The Early Warning Score (EWS) is a clinical monitoring system used in inpatient settings to detect early signs of patient deterioration. EWS is expected to improve hospital service quality, particularly in patient safety. This article aims to review the impact of EWS implementation on the quality of inpatient care in hospitals in Indonesia using a literature review method. Data were obtained from six open access scientific articles published in 2020-2026 through searches on Google Scholar, ScienceDirect, and Garuda Portal with the keywords "Early Warning Score" AND "Service Quality" AND "Inpatient" AND "Hospital". The review shows that EWS holds great potential in reducing mortality and enhancing early detection of clinical deterioration. However, its effectiveness highly depends on system quality, healthcare provider engagement, and organizational support. Low usage rates of EWS remain a significant barrier to achieving its full benefits. EWS implementation contributes positively to the quality of inpatient services, but optimal application is necessary to maximize its clinical impact.